2022
DOI: 10.1038/s41598-022-18255-z
|View full text |Cite
|
Sign up to set email alerts
|

Improving taste sensitivity in healthy adults using taste recall training: a randomized controlled trial

Abstract: Although many patients suffer from taste disorder, methods to improve taste sensitivity are limited. To develop a taste recall training method to improve the perception of taste, 42 healthy individuals were randomly assigned to either the training or the control group. Using the filter paper disc method, participants in the training group were asked to match the four tastes (sweetness, saltiness, sourness, and bitterness) between those of taste recognition thresholds and those of a one-step higher concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…In the current study, the correct identification of supra-threshold tastants was a prerequisite for participation. However, a recent study on taste rehabilitation has indicated that gustatory sensitivity can be increased through taste training [ 40 ]. As such, some patients may benefit from focused gustatory training before engaging in cooking using “The 5T’s”.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the correct identification of supra-threshold tastants was a prerequisite for participation. However, a recent study on taste rehabilitation has indicated that gustatory sensitivity can be increased through taste training [ 40 ]. As such, some patients may benefit from focused gustatory training before engaging in cooking using “The 5T’s”.…”
Section: Discussionmentioning
confidence: 99%